Foaming material as well as preparation method and application thereof
By adding antibacterial agents to polyurethane matrix and surface fluoride, the existing polyurethane foam material bubbles are uniform in size, the surface viscosity is large, and the antibacterial properties are not available, and the good antibacterial and low of the foaming materials are achieved. Surface viscosity and bubbles are uniform, suitable for products that are in contact with organisms.
Patent Information
- Application Number
- CN202310891171.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-21
AI Technical Summary
The existing polyurethane foaming materials have problems such as poor cell size uniformity, large surface viscosity and lack of antibacterial properties, which limit their application scope.
By adding antibacterial agents such as ε-polyinine to polyurethane, and cross-linked gels in a non-water system, a gel-type forest body with a foam is formed, and then surface fluoride is performed. Antibacterial, low surface viscosity and uniform foaming material.
It achieves good antibacterial properties, low surface viscosity and uniform cell size of the foam material. It is suitable for products that come into contact with living organisms, such as earphone ear caps. It has healthy antibacterial properties, smoothness and dirt resistance, breathability and water permeability, and sound insulation and noise reduction. and other advantages.
Smart Images

Figure CN119331198A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of foaming materials, and in particular to a foaming material and a preparation method and application thereof. Background Art
[0002] Existing polyurethane foam materials generally have problems such as poor uniformity of pore size, high surface viscosity and lack of antibacterial properties, which need to be solved urgently. Summary of the invention
[0003] The present application provides a foaming material and a preparation method and application thereof. The foaming material has good antibacterial properties, uniform pore size, low surface viscosity and other characteristics, and can effectively overcome the defects of the prior art.
[0004] In one aspect of the present application, a foaming material is provided, comprising a polyurethane matrix and an antibacterial agent present in the polyurethane matrix, wherein the surface water contact angle of the foaming material is greater than 90°; the foaming material has pores, and the size of the pores is less than 200 μm.
[0005] In some embodiments, the size of the cells in the foamed material is between 10 μm and 161 μm.
[0006] In some embodiments, the foaming material is a slow-rebound sponge, and its rebound recovery time is not less than 4 seconds.
[0007] In some embodiments, the antimicrobial agent comprises ε-polylysine.
[0008] In some embodiments, a catalyst is further contained in the polyurethane matrix, and the catalyst includes an organic bismuth catalyst and a tertiary amine catalyst.
[0009] In some embodiments, a foam stabilizer is further contained in the polyurethane matrix, and the foam stabilizer includes polyether-modified siloxane.
[0010] In some embodiments, the raw materials of the polyurethane matrix include polyether polyols and MDI-based isocyanate, and the polyether polyols include a first polyether polyol with a hydroxyl value of (228-248) mg KOH / g, a second polyether polyol with a hydroxyl value of (28-40) mg KOH / g, and a third polyether polyol with a hydroxyl value of (22-32) mg KOH / g.
[0011] In some embodiments, the ratio of the mass of the first polyether polyol to the total mass of the polyether polyols is (65-95):100; and / or, the ratio of the mass of the second polyether polyol to the total mass of the polyether polyols is (2.5-17.5):100; and / or, the ratio of the mass of the third polyether polyol to the total mass of the polyether polyols is (2.5-17.5):100.
[0012] In some embodiments, a fluorinated layer is formed on the surface of the foamed material.
[0013] Another aspect of the present application provides a method for preparing the above-mentioned foaming material, comprising the following steps: cross-linking a polyether polyol and an MDI-based isocyanate in the presence of an antibacterial agent, a catalyst and a foam leveling agent in a non-aqueous environment to form a gel, and introducing gas therein to form pores to obtain a gel-type precursor having pores; subjecting the gel-type precursor to a surface fluorination treatment to obtain the foaming material; wherein the polyether polyol comprises a first polyether polyol having a hydroxyl value of (228-248) mgKOH / g, a second polyether polyol having a hydroxyl value of (28-40) mgKOH / g and a third polyether polyol having a hydroxyl value of (22-32) mgKOH / g; and the catalyst comprises an organic bismuth catalyst and a tertiary amine catalyst.
[0014] In some embodiments, the ratio of the mass of the first polyether polyol to the total mass of the polyether polyols is (65-95):100; and / or, the ratio of the mass of the second polyether polyol to the total mass of the polyether polyols is (2.5-17.5):100; and / or, the ratio of the mass of the third polyether polyol to the total mass of the polyether polyols is (2.5-17.5):100.
[0015] In some embodiments, the antimicrobial agent comprises ε-polylysine.
[0016] In some embodiments, the foam stabilizer includes polyether-modified siloxane.
[0017] In some embodiments, the process of cross-linking the gel includes: mixing the polyether polyol, the antibacterial agent, the catalyst and the foam leveling agent to obtain a first mixed system; mixing the first mixed system with the MDI-based isocyanate and introducing the gas therein to obtain a second mixed system; subjecting the second mixed system to a shaping treatment, and performing gelation and pore growth shaping through the shaping treatment to obtain a gel-type intermediate with pores formed therein; subjecting the gel-type intermediate to a aging treatment to obtain the gel-type precursor.
[0018] In some embodiments, the setting treatment conditions are: temperature of 40°C to 60°C, time of 10 min to 20 min; and / or, the aging treatment conditions are: temperature of 60°C to 80°C, time of 30 min to 60 min.
[0019] In some embodiments, the gel-type precursor is contacted with a mixed gas containing fluorine and oxygen to perform the surface fluorination treatment, and / or the temperature of the surface fluorination treatment is 40° C. to 60° C., and the time of the surface fluorination treatment is 10 min to 30 min.
[0020] In another aspect of the present application, a composite material is provided, comprising a substrate, and a foam material present on the surface of the substrate, wherein the foam material comprises the foam material mentioned above or the foam material prepared according to the preparation method mentioned above.
[0021] In some embodiments, the composite material is an ear cap of an earphone, or a sponge pad for a wearable augmented reality device or a wearable virtual reality device.
[0022] In another aspect of the present application, a wearable device is provided, comprising the above-mentioned composite material.
[0023] In some embodiments, the wearable device includes headphones, a wearable augmented reality device, or a wearable virtual reality device.
[0024] In another aspect of the present application, a method for preparing the composite material is provided, comprising the following steps: forming the foaming material on the surface of the substrate according to the above preparation method to obtain the composite material.
[0025] In some embodiments, after the adhesive is coated on the surface of the substrate, the polyether polyol and the MDI-based isocyanate are cross-linked and gelled on the surface of the substrate in the presence of an antibacterial agent, a catalyst and a foam leveler in a non-aqueous environment.
[0026] The foam material provided by the present application is a polyurethane foam material (or polyurethane foam or polyurethane sponge), and an antibacterial agent exists in the polyurethane matrix, so that the foam material has good antibacterial properties, and the antibacterial rate can reach 90%, or even 95% or 96% or more; at the same time, the surface water contact angle of the foam material is greater than 90°, the surface viscosity is low, and it is not easy to be contaminated with dust and other impurities, thereby improving its dirt resistance and surface smoothness; at the same time, the number of pores with a size greater than 200 μm per square centimeter of the foam material is less than 2 (i.e., N < 2 / cm 2 ), so that the size of the pores in the foamed material is basically distributed in the range of less than 200 μm, showing good pore size uniformity.
[0027] Therefore, the foaming material provided by the present application has the characteristics of good antibacterial property, low surface viscosity, uniform pore size, good air permeability and water permeability, as well as sound insulation and noise reduction, and has a wide range of applications. For example, it can be used to form products that come into contact with organisms, such as wearable devices, specifically earphone ear caps, sponge pads for wearable augmented reality devices (AR helmets) or wearable virtual reality devices (VR helmets), etc., which can make these products have the advantages of healthy antibacterial, smooth and dirt-resistant, air permeable and water permeable, beautiful appearance, and sound insulation and noise reduction. For example, after the ear cap formed by the foaming material is assembled to the in-ear earphone, the ear cap has good air permeability and water permeability, and can ensure the dryness and freshness of the ear canal after the human body wears it (after the human body wears it for 1 hour (h), the humidity of the ear canal is within 85% (i.e., not more than 85%)), which is healthier. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 A schematic diagram of the process of preparing polyurethane foam material by chemical water foaming;
[0029] Figure 2 This is a scanning electron microscope image of a polyurethane material that has not formed an effective cellular structure;
[0030] Figure 3 This is a scanning electron microscope image of a polyurethane foam material with cell collapse;
[0031] Figure 4 This is a schematic diagram of the chemical water foaming process;
[0032] Figure 5 This is a schematic diagram of the cell structure of an embodiment of the present application;
[0033] Figure 6 This is a schematic diagram of the earphone ear cap structure of an embodiment of the present application.
[0034] Explanation of reference numerals: 1: substrate; 10: accommodating area; 110: first limiting groove; 120: second limiting groove; 101: raised portion; 2: foam material; 100: lower side (bottom); 200: upper side. DETAILED DESCRIPTION
[0035] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0036] Existing polyurethane foam materials generally have problems such as poor uniformity of pore size, high surface stickiness and lack of antibacterial properties, which limit their application.
[0037] Specifically, polyurethane foam materials are usually made by chemical water foaming, such as Figure 1 As shown, the raw materials may include isocyanates, polyols (such as Figure 1 The polyol 1 and polyol 2 shown in the figure), water (foaming agent), catalyst, chain extender, cell opener, etc. The catalyst is usually a tin (Sn) catalyst, a zirconium (Zr) catalyst, a titanium (Ti) catalyst and DBU Etc. Among them, isocyanates cross-link gel with polyols under the action of catalysts to form a gel, and at the same time, isocyanates react with water to generate carbon dioxide (CO2) to expand and foam the formed gel. The gel (or melt) formed by cross-linking the gel has greater strength and can cover the generated CO2, thereby forming a cellular structure. After the cross-linked gel is shaped, it can be further turned into an oven for aging, for example, at a temperature of 40°C to 80°C and a time of 10min to 60min. During the aging process, the incompletely reacted isocyanates will continue to react with the polyols and water to form the final polyurethane foam material. Among them, the reaction formula of the cross-linked gel and the foaming reaction (i.e., the reaction of isocyanates and water (H2O) to generate CO2) is shown as follows:
[0038]
[0039] In the chemical water foaming process, cross-linking gel and foaming reaction are carried out simultaneously. When the gel speed is too fast (the gel speed is faster than the foaming speed), the viscosity of the formed gel increases rapidly, and its strength is relatively large. The formation of pores is restricted, and even the gel cannot form a pore structure (such as Figure 2 When the gelation speed is too slow (the gelation speed is slower than the foaming speed), the viscosity of the gel is low and its strength is small, which cannot cover and limit the formation of pores, and will also lead to the failure to form a good pore structure. The product morphology usually shows the phenomenon of pore collapse (such as Figure 3 As shown). Therefore, it is usually difficult to control the cell structure in the process of preparing polyurethane foam materials by chemical water foaming process. In this process, isocyanates are contacted with water in the presence of a catalyst to react chemically to produce CO2 for foaming. If water and isocyanates are not mixed evenly, the resulting cells will be unevenly distributed and large cell structures (larger than 200 μm in size) will be easily formed, resulting in problems such as uneven cell distribution and large size differences in polyurethane foam materials (such as Figure 1 As shown, large cells and small cells with large size differences are formed in the foamed material).
[0040] In addition, if Figure 4As shown, the chemical foaming process is carried out in a container (such as a mold for forming a preset shape of foam), that is, isocyanate, polyol, water (foaming agent), catalyst, chain extender, cell opener and other components are placed in the container for cross-linking gel and foaming. Usually, nucleation points are formed first in the reaction system (i.e. nucleation), and then pores grow at the nucleation points (i.e. foaming). Figure 4 As shown, in this process, the gravity exerted on various regions of the reaction system is uneven. Generally, the regions closer to the bottom are subjected to greater gravity, while the regions closer to the top of the container are subjected to smaller gravity. As a result, the cells formed in the regions near the bottom of the container tend to be smaller, while the cells formed in the regions near the top of the container tend to be larger, resulting in uneven cell sizes in various regions of the foamed material.
[0041] Therefore, the above-mentioned polyurethane foam material has the problem of uneven pore distribution, wherein the size of large pores is usually larger than 200 μm, resulting in large differences in pore sizes in the polyurethane foam material, affecting the performance and appearance of the polyurethane foam material.
[0042] In addition, the above-mentioned polyurethane foam material has problems such as being sticky and easily dirty on the surface and not having antibacterial properties. When it is used to form products that come into contact with biological bodies, such as earphone ear caps, it is not smooth, dirt-resistant and healthy enough.
[0043] On the other hand, with the development of society, people's health awareness is also gradually improving, and higher requirements are put forward for the health, comfort and functionality of electronic materials. Take the ear caps of headphones as an example. The ear caps of headphones are suitable for being installed on the earphone heads of in-ear headphones. When used, they are in direct contact with the human ear canal. They are usually required to have slow rebound comfort, healthy antibacterial, sound insulation and noise reduction, smooth and dirt-resistant properties. However, most of the current ear cap materials are silicone materials (silicone rubber (SiR)), which have poor sound insulation and noise reduction performance, and after long-term use, they are prone to problems such as stickiness and yellowing. At the same time, they have poor water permeability and air permeability, resulting in the ear canal being relatively moist after the human body wears the headphones for a long time, which is easy to cause itching and stickiness when touching the ear caps.
[0044] Polyurethane foam materials have the advantages of adjustable performance. They are mainly composed of isocyanate as the main component, and the strength, modulus, softness and twistability of the polyurethane foam materials formed by the molecular weight of the polyol or polyester used can be regulated, and they have gradually attracted widespread attention. The performance adjustability of polyurethane foam materials is relatively wide, and polyurethane foam materials with good water permeability and air permeability and sound insulation and noise reduction effects can be formed by regulating their formula and process conditions. However, as mentioned above, existing polyurethane foam materials generally have problems such as poor uniformity of pore size, high surface viscosity (poor smoothness and dirt resistance), and lack of antibacterial properties, which need to be solved urgently.
[0045] In view of this, an embodiment of the present application provides a foaming material, including a polyurethane matrix and an antibacterial agent present in the polyurethane matrix, wherein the surface water contact angle of the foaming material is greater than 90°; the foaming material has pores, and the size of the pores is less than 200 μm.
[0046] The foaming material provided in the embodiment of the present application is a polyurethane foam with polyurethane (PU) as the matrix, in which an antibacterial agent is present, so that the foaming material has good antibacterial properties, and the antibacterial rate can reach 90%, or even 95% or 96% or more; at the same time, the surface water contact angle of the foaming material is greater than 90°, the surface viscosity is low, and it is not easily contaminated by dust and other impurities, thereby improving its dirt resistance and surface smoothness; at the same time, the size distribution of the pores in the foaming material is within the range of less than 200μm, and there are basically no large pores with a size greater than 200μm, and the pores are uniform and of uniform size.
[0047] Therefore, the foaming material provided in the embodiments of the present application has the characteristics of good antibacterial properties, low surface viscosity, uniform pore size, good air permeability and water permeability, as well as sound insulation and noise reduction. It can be used to form products that come into contact with organisms, such as earphone ear caps, so that these products have the advantages of healthy antibacterial properties (for example, the inhibition rate of pathogens such as Escherichia coli can be as high as 90%, or even 95% or 96% or more), smooth and dirt-resistant, air permeable and water permeable, beautiful appearance, and sound insulation and noise reduction.
[0048] The size of the pore (or pore diameter) is the maximum size of the pore, i.e., the length L of the longest part of the pore (e.g. Figure 5 shown).
[0049] The present application can measure the size of the pores in the foam material by conventional methods in the art, for example, the foam material is cut, and the pore morphology of the cut section (cross section) is observed under a magnification of 100 times using an optical microscope, or the morphology of the part of the foam material that is not fluorinated (such as the bottom of the earphone ear cap described below) in the product containing the foam material (such as the earphone ear cap, etc.) is measured to measure the pore size. In specific implementation, the pore size of a certain area can be counted and converted into an average of 1 cm 2 The number of cells in the area with a size less than 200 μm, when the foaming material meets N < 2 / cm 2 When (N represents the number of cells with a size larger than 200 μm per square centimeter of the foam material), the number of cells with a size larger than 200 μm per square centimeter is less than 2 (i.e., N < 2 cells / cm 2 ), it can be considered that the pore size distribution in the foamed material is within the range of less than 200 μm, and there are basically no large pores with a size greater than 200 μm.
[0050] Generally, in the above-mentioned foaming material, the size of the pores is between 10μm and 161μm, that is, the size of the smallest pore is not less than 10μm (that is, the size of the pores in the foaming material is not less than 10μm), the size of the largest pore is not greater than 161μm (that is, the size of the pores in the foaming material is not greater than 161μm), and the difference in size between any two pores in the foaming material is basically not greater than 151μm (the difference in size between the largest pore and the smallest pore is not greater than 151μm, for example, about 151μm).
[0051] Specifically, the above-mentioned foaming material is a slow-rebound sponge, and its rebound recovery time is not less than 4 seconds. That is, after the foaming material is squeezed to the maximum extent, the time it takes to recover to its original natural state is not less than 4 seconds. The foaming material has good slow-rebound characteristics, so that products such as earphones and earmuffs formed by the foaming material have better comfort.
[0052] The maximum degree generally refers to the degree to which the foaming material is squeezed to the point where it cannot be squeezed further but the foaming material will not be damaged. The present application can measure the rebound recovery time of the above foaming material by the conventional method for measuring the recovery time of slow rebound sponge in the art. In specific implementation, for example, the foaming material is squeezed to the maximum degree with fingers and then released. At the same time, a timer such as a stopwatch is used to record the time for the foaming material to return to its original state, so as to measure its rebound recovery time.
[0053] The polyurethane matrix is the main component of the foaming material, and its raw materials may include polyether polyols and MDI-based isocyanates. The polyurethane matrix can be specifically formed by cross-linking gels of these raw materials. The polyether polyols may include a first polyether polyol with a hydroxyl value of (228-248) mg KOH / g, a second polyether polyol with a hydroxyl value of (28-40) mg KOH / g, and a third polyether polyol with a hydroxyl value of (22-32) mg KOH / g, which is beneficial for the foaming material to have good viscoelasticity, so that it has both good slow rebound characteristics (rebound recovery time is less than 4s) and low surface viscosity.
[0054] Illustratively, the hydroxyl value of the first polyether polyol can be 228 mg KOH / g, 230 mg KOH / g, 233 mg KOH / g, 235 mg KOH / g, 238 mg KOH / g, 240 mg KOH / g, 243 mg KOH / g, 245 mg KOH / g, 248 mg KOH / g, or a range consisting of any two thereof.
[0055] Illustratively, the hydroxyl value of the second polyether polyol can be 28 mg KOH / g, 30 mg KOH / g, 32 mg KOH / g, 33.5 mg KOH / g, 35 mg KOH / g, 38 mg KOH / g, 40 mg KOH / g, or a range consisting of any two thereof.
[0056] Illustratively, the hydroxyl value of the third polyether polyol may be in the range of 22 mg KOH / g, 25 mg KOH / g, 28 mg KOH / g, 30 mg KOH / g, 32 mg KOH / g, or any two thereof.
[0057] The first polyether polyol, the second polyether polyol and the third polyether polyol can be purchased commercially or prepared in-house. For example, the first polyether polyol is VE7321 from Jiahua Chemical Co., Ltd., the second polyether polyol is Puranol F1623 from Jiahua Chemical Co., Ltd., and the third polyether polyol is Puranol PP2045B from Jiahua Chemical Co., Ltd.
[0058] In some embodiments, the ratio of the mass of the first polyether polyol to the total mass of the polyether polyols can be (65-95):100, for example, 65:100, 68:100, 70:100, 73:100, 75:100, 78:100, 80:100, 83:100, 85:100, 88:100, 90:100, 93:100, 95:100 or a range consisting of any two of them.
[0059] In some embodiments, the ratio of the mass of the second polyether polyol to the total mass of the polyether polyol can be (2.5-17.5):100, for example, 2.5:100, 3:100, 5:100, 8:100, 10:100, 13:100, 15:100, 17:100, 17.5:100 or a range consisting of any two of them.
[0060] In some embodiments, the ratio of the mass of the third polyether polyol to the total mass of the polyether polyols can be (2.5-17.5):100, for example, 2.5:100, 3:100, 5:100, 8:100, 10:100, 13:100, 15:100, 17:100, 17.5:100 or a range consisting of any two of them.
[0061] Specifically, the total mass of the polyether polyol refers to the sum of the masses of all polyether polyols. For example, if the polyether polyol is composed of the first polyether polyol, the second polyether polyol and the third polyether polyol, the total mass of the polyether polyol refers to the sum of the masses of the three polyether polyols (i.e., the total mass of the polyether polyol = the mass of the first polyether polyol + the mass of the second polyether polyol + the mass of the third polyether polyol). The above formula is conducive to further improving the slow rebound characteristics and low surface viscosity of the foaming material.
[0062] In addition, the amounts of MDI-based isocyanate and polyether polyol can be conventional amounts of these materials in the art. For example, the amounts of MDI-based isocyanate and polyether polyol can satisfy NCO / OH=a:1 (i.e., the molar ratio of the NCO group of the above-mentioned MDI-based isocyanate to the hydroxyl (OH) group of the polyether polyol is a:1), 0.3<a<1.5, and the ratio of the mass of MDI-based isocyanate to the total mass of the polyether polyol can be 30% to 50%, for example, 30%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 50% or a range consisting of any two of them.
[0063] The embodiments of the present application may adopt conventional MDI-based isocyanates in the art. For example, the mass content of NCO groups in the above-mentioned MDI-based isocyanates may be 20% to 35%. For example, the isocyanate components of the above-mentioned foaming material (i.e., MDI-based isocyanates) are all diphenylmethane diisocyanate (Methylenediphenyl Diisocyanate, MDI), which may specifically include one or more MDI isomers, for example, including one or more of 4,4'-MDI, 2,4'-MDI, and 2,2'-MDI (i.e., the above-mentioned MDI-based isocyanate may be a single MDI isomer component or a mixture of multiple MDI isomers).
[0064] In specific implementation, modified MDI-based isocyanate can be used. The modified MDI-based isocyanate used can be liquid, which can specifically be a mixture of multiple MDI isomers. It can be commercially available or homemade. For example, modified isocyanate 8019 from Wanhua Chemical Group Co., Ltd. can be used.
[0065] The antimicrobial agent can be an antimicrobial component capable of inhibiting pathogens such as Escherichia coli, which can be grafted into the polyurethane matrix through chemical bonds to exhibit antimicrobial properties. In specific implementation, polyether polyol and MDI-based isocyanate can be cross-linked and gelled in the presence of the antimicrobial agent to form a polyurethane matrix and the antimicrobial agent present in the polyurethane matrix.
[0066] In some embodiments, the antimicrobial agent may include ε-polylysine, which may be introduced into the foaming material to impart good antimicrobial properties to the foaming material, with an inhibition rate of up to 90%, or even 95% or 96% or more, against pathogens such as Escherichia coli.
[0067] In the embodiments of the present application, there is no particular restriction on the content of the antibacterial agent in the foaming material, as long as the antibacterial effect that meets the preset requirements can be achieved (for example, the antibacterial rate of the foaming material against pathogens such as Escherichia coli is as high as 90% or more). For example, the ratio of the mass of the antibacterial agent to the total mass of the polyether polyol can be (0.01-0.2):100.
[0068] In addition, the foaming material may also contain a catalyst present in the polyurethane matrix. In specific implementation, the polyether polyol and the MDI-based isocyanate may be crosslinked and gelled in the presence of the catalyst to form the polyurethane matrix and the catalyst present in the polyurethane matrix.
[0069] Specifically, the catalyst may include an organic bismuth catalyst and a tertiary amine catalyst. The use of the organic bismuth catalyst and the tertiary amine catalyst is beneficial to the uniformity of the pores of the foaming material and other properties.
[0070] The organic bismuth catalyst includes, for example, bismuth isooctanoate and / or bismuth neodecanoate, etc. The organic bismuth catalyst used can be purchased commercially or prepared by conventional methods in the art, for example, a commercial organic bismuth catalyst of grade MC-710 from Maitu Advanced Materials Group Co., Ltd. can be used.
[0071] Among them, the tertiary amine catalyst includes, for example, the reaction product of substituted alkyl-(polyalkyl-substituted) alkyl polyalkyl-alkanediamine and oxidized olefins. The tertiary amine catalyst used can be commercially available or homemade by conventional methods in the art, for example, a commercial tertiary amine catalyst of grade NE1550 from Evonik Specialty Chemicals (Shanghai) Co., Ltd. can be used.
[0072] In specific implementation, the amount of catalyst can be regulated according to requirements such as reaction efficiency. For example, the ratio of the mass of the organic bismuth catalyst to the total mass of the polyether polyol can be (0.01-0.2):100, and the ratio of the mass of the tertiary amine catalyst to the total mass of the polyether polyol can be (0.05-2):100, but is not limited thereto.
[0073] In addition, the foaming material may also contain a foam leveling agent in the polyurethane matrix. In a specific implementation, the polyether polyol and the MDI-based isocyanate may be crosslinked and gelled in the presence of the foam leveling agent to form a polyurethane matrix and the foam leveling agent in the polyurethane matrix. The foam leveling agent may further improve the properties of the foam cells in the foaming material, such as uniformity and uniform size.
[0074] Specifically, the ratio of the mass of the foam leveling agent to the total mass of the polyether polyol may be (0.3-1):100, but is not limited thereto.
[0075] Specifically, the foam leveling agent may include polyether-modified siloxane, which may be purchased commercially or prepared by conventional methods in the art, such as TEGOSTAB B 8930 from Evonik Specialty Chemicals (Shanghai) Co., Ltd., and the like, without particular limitation.
[0076] In addition, a fluoride layer may be formed on the surface of the foamed material, that is, fluorine element exists in the surface area of the foamed material to form a fluoride layer. By forming the fluoride layer, the surface viscosity of the foamed material can be reduced, making its surface smooth and resistant to dirt.
[0077] In specific implementation, the foaming material can be subjected to surface fluorination treatment to introduce fluorine elements on its surface to form a fluorinated layer. Specifically, after the cross-linking gel of the polyether polyol and the MDI-based isocyanate is completed, the obtained gel-type precursor with a cellular structure can be contacted with fluorine gas for fluorination treatment to form a fluorinated layer on its surface to obtain the foaming material.
[0078] The embodiment of the present application can form pores by physical foaming, that is, during the cross-linking gelation process of the polyether polyol and the MDI-based isocyanate, air or other gases are introduced therein to form pores, without introducing water, and forming pores by CO2 generated by the reaction of the MDI-based isocyanate and water. Compared with the conventional chemical water foaming method, the embodiment of the present application forms pores by physical foaming, which can make the foaming material have advantages such as uniform pore distribution and uniform size.
[0079] Specifically, the foaming material can be prepared according to a process including the following steps: cross-linking gelation of polyether polyol and MDI isocyanate in the presence of antibacterial agent, catalyst and foam leveling agent to form a polyurethane matrix, and antibacterial agent, catalyst and foam leveling agent and other components present in the polyurethane matrix, and by passing gas therein to form pores, a gel-type precursor with pores is obtained; then the gel-type precursor is contacted with fluorine gas for fluorination treatment to form a fluorinated layer to obtain the foaming material. The foaming material thus obtained has the advantages of uniform pores, no large pores (the pore size is basically distributed in the range of less than 200 μm), uniform pore size, good air permeability and water permeability, and good slow resilience, antibacterial property, smooth and dirt-resistant (low surface viscosity), sound insulation and noise reduction. Among them, the cross-linking gel process can be carried out in a non-aqueous environment, that is, no water is added to the system for cross-linking gel (no need to generate CO2 through the reaction of MDI isocyanate and water to form pores).
[0080] An embodiment of the present application also provides a method for preparing the above-mentioned foaming material, comprising the following steps: cross-linking polyether polyol and MDI-based isocyanate to form a gel in the presence of an antibacterial agent, a catalyst and a foaming agent, and forming pores by introducing gas therein to obtain a gel-type precursor having pores; and surface fluorination treatment of the gel-type precursor to obtain a foaming material.
[0081] In specific implementation, a mixed system containing polyether polyol, MDI-based isocyanate, antibacterial agent, catalyst and foam leveling agent (such as the second mixed system described below) can be crosslinked and gelled in a non-aqueous environment, and gas can be introduced into the mixed system to form pores to obtain a gel-type precursor with pores. Generally, polyether polyol, antibacterial agent, catalyst and foam leveling agent can be mixed, then mixed with MDI-based isocyanate, and gas can be introduced into the mixed system, and then crosslinked and gelled. During the crosslinking and gelling process, the system gels, and the pores grow and shape to form a gel-type precursor with pores. Among them, the above-mentioned mixed system is usually liquid, and specifically, liquid MDI-based isocyanate and other components can be used.
[0082] In some specific embodiments, the preparation process of the above-mentioned gel-type precursor with pores may include: mixing polyether polyol, antibacterial agent, catalyst and foam leveling agent to obtain a first mixed system; mixing the first mixed system with MDI-based isocyanate, and introducing gas therein to obtain a second mixed system; subjecting the second mixed system to a shaping treatment, and performing gel and pore growth shaping through the shaping treatment to obtain a gel-type intermediate with pores formed therein; subjecting the gel-type intermediate to a aging treatment to obtain a gel-type precursor.
[0083] Among them, the conditions for the setting treatment can be: a temperature of 40°C to 60°C, for example, 40°C, 43°C, 45°C, 48°C, 50°C, 53°C, 55°C, 58°C, 60°C or a range consisting of any two thereof, and a time of 10min to 20min, for example, 10min, 12min, 15min, 18min, 20min or a range consisting of any two thereof.
[0084] In a specific implementation, the polyether polyol, antibacterial agent, catalyst and foaming agent can be placed in a first container and stirred and mixed under a high-speed stirring state at a rotation speed of 1800-2200rpm / min (such as 2000rpm / min). Specifically, the stirring and mixing can be carried out in a high-speed stirrer, and the stirring time can be 1-5min (such as about 2min) to obtain a first mixed system.
[0085] In addition, before the first mixed system and the MDI-based isocyanate are mixed, the temperatures of the two can be maintained at a preset molding treatment temperature (40°C to 60°C). Specifically, the first mixed system is placed in a first material tank, and the MDI-based isocyanate is placed in a second material tank. The first material tank is kept at a preset molding treatment temperature (40°C to 60°C), and the second material tank is kept at a preset molding temperature (40°C to 60°C). Then, the first mixed system in the first material tank and the MDI-based isocyanate in the second material tank are pumped into a mixing head or other mixing equipment for mixing, and at the same time, air or other gases are pumped into the mixing equipment for mixing to obtain a second mixed system. The second mixed system can be in a slurry state.
[0086] In addition, the temperature and / or time of the aging treatment may generally be greater than the temperature of the setting treatment. In some embodiments, the aging conditions may be: the temperature is 60°C to 80°C, for example, 60°C, 63°C, 65°C, 68°C, 70°C, 73°C, 75°C, 78°C, 80°C or a range consisting of any two thereof; the time may be 30min to 60min, for example, 30min, 35min, 40min, 45min, 50min, 55min, 60min or a range consisting of any two thereof.
[0087] In the above process, by first performing the shaping treatment and then the aging treatment, the production efficiency can be improved, while ensuring that the MDI-based isocyanate reacts more fully and optimizing the performance of the polyurethane foam material. Specifically, the above cross-linking gel process can be carried out in a mold to form a polyurethane foam material product (such as earphone ear caps, etc.) of a preset shape. Specifically, the second mixed system can be placed in the mold for shaping treatment. After the shaping treatment is completed, the gel-type precursor is taken out of the mold and placed in a heating device such as an oven for aging treatment. In this way, the shaping treatment is first performed to facilitate demolding as soon as possible, improve production efficiency, and then the aging treatment is performed, which can further ensure that the MDI-based isocyanate reacts completely and improve the performance of the polyurethane foam material.
[0088] In the above preparation process, by subjecting the gel-type precursor to surface fluorination treatment, a fluoride layer can be formed on its surface, thereby reducing the surface viscosity of the foamed material obtained and improving its smooth and dirt-resistant properties. The gel-type precursor can be subjected to surface fluorination treatment in the presence of oxygen. In some embodiments, the gel-type precursor can be contacted with a mixed gas containing fluorine gas and oxygen to perform surface fluorination treatment. The surface fluorination treatment temperature can be 40°C to 60°C, such as 40°C, 43°C, 45°C, 48°C, 50°C, 53°C, 55°C, 58°C, 60°C or any two thereof. The surface fluorination treatment time is 10min to 30min, such as 10min, 13min, 15min, 18min, 20min, 23min, 25min, 28min, 30min or any two thereof.
[0089] In the above preparation process, MDI isocyanate and polyether polyol cross-linked gel form a polyurethane matrix, and the antibacterial agent, catalyst and foaming agent will remain in the polyurethane matrix to form a foaming material including the polyurethane matrix and the antibacterial agent, catalyst and foaming agent present in the polyurethane matrix.
[0090] As mentioned above, the polyether polyol includes a first polyether polyol having a hydroxyl value of (228-248) mg KOH / g, a second polyether polyol having a hydroxyl value of (28-40) mg KOH / g, and a third polyether polyol having a hydroxyl value of (22-32) mg KOH / g. The ratio of the mass of the first polyether polyol to the total mass of the polyether polyols may be (65-95):100, the ratio of the mass of the second polyether polyol to the total mass of the polyether polyols may be (2.5-17.5):100, and the ratio of the mass of the third polyether polyol to the total mass of the polyether polyols may be (2.5-17.5):100. For details, please refer to the above, and no further details will be given here.
[0091] As mentioned above, the antimicrobial agent may include ε-polylysine, the catalyst may include an organic bismuth catalyst and a tertiary amine catalyst, and the foam leveling agent may include polyether-modified siloxane.
[0092] The present application also provides a composite material, including a substrate and a foam material on the surface of the substrate, wherein the foam material includes the above-mentioned foaming material. The composite material has the same advantages as the above-mentioned foaming material, which will not be described in detail.
[0093] Specifically, the substrate may include silicone and / or plastic, for example, a silicone substrate or a plastic substrate, but is not limited thereto.
[0094] Specifically, the composite material can be used in wearable devices, wherein the foaming material is located on the surface of the wearable device that contacts the human body, that is, when the human body wears the wearable device, the foaming material directly contacts the human body. For example, the composite material can be specifically used for earphone ear caps, sponge pads for wearable augmented reality devices (AR helmets) or wearable virtual reality devices (VR helmets), etc.
[0095] Taking the earphone cap as an example, the earphone cap is used to be put on the earphone of the in-ear earphone and directly contact the human ear canal. Figure 6 As shown, the earphone ear cap of the embodiment of the present application includes the above-mentioned foam material 2 and a substrate 1. The substrate 1 can specifically be a silicone substrate. The substrate 1 is located on the inner side of the ear cap to stabilize and fix the ear cap. Its structure is configured to be snapped with the contour of the earphone, that is, the substrate 1 is surrounded by a receiving area 10. When the earphone ear cap is put on the earphone, the earphone is inserted into the receiving area 10 and snapped with the substrate 1 surrounded by the receiving area 10 to fix the earphone and the earphone ear cap together; the foam material 2 is located on the outer side of the ear cap, that is, the foam material 2 is arranged on the surface of the substrate 1 away from the receiving area 10. When the earphone ear cap is put on the earphone, after the human body wears the earphone, the foam material 2 of the earphone ear cap directly contacts the human ear canal, which has the effects of softness, comfort, sound insulation and noise reduction.
[0096] Figure 6 The earphone ear cap structure of an embodiment is shown exemplarily. Figure 6 The earphone ear cap has an upper side 200 and a lower side 100 relative to each other, and the lower side (i.e., the bottom) 100 is provided with an opening communicating with the accommodating area 10. When the earphone ear cap is put on the earphone, the earphone is inserted into the accommodating area 10 from the opening of the lower side 100 of the earphone ear cap. The substrate 1 is provided with a first limiting groove 110 and a second limiting groove 120 communicating with the accommodating area 10 on one side (inner side) facing the accommodating area 10. The first limiting groove 110 is provided on the peripheral side of the substrate 1, and can be specifically extended outward on the substrate 1 along the direction from the accommodating area 10 to the substrate 1 (i.e., from the accommodating area 10). The first convex groove 110 is provided on the upper side of the substrate 1, and the second convex groove 12 ...
[0097] In addition, if Figure 6As shown, a protrusion 101 may also be provided on the side of the substrate 1 facing away from the accommodating area 10, and the protrusion 101 extends toward the foam material 2 and is embedded in the foam material 2. The protrusion 101 may specifically be provided on the side of the substrate 1 facing the upper side 200 of the ear cap of the headphone, that is, the protrusion 101 is provided on the upper side of the substrate 1, and may be formed by the substrate 1 extending from the lower side 100 to the upper side 200 of the ear cap of the headphone.
[0098] Among them, the first limiting groove 110 can be one or more, or the first limiting groove 110 is arranged on the circumferential side of the inner side of the substrate 1, and the second limiting groove 120 can be one or more. There is no special limitation on this. In specific implementation, the substrate 1 of a preset shape can be formed according to the contour of the earphone, so that it has a matching accommodating area 10, a first limiting groove 110 and a second limiting groove 120 and other structures to form an earphone ear cap with a preset structure and shape.
[0099] In addition, the composite material may further include an adhesive layer disposed between the substrate 1 and the foam material 2, which may further improve the structural stability and other properties of the composite material. In specific implementation, the adhesive layer may be formed using a conventional glue material (adhesive) suitable for bonding in the art, such as MW-221 from Magotan.
[0100] The earphone ear caps of the embodiments of the present application have at least the following advantages: (1) The pore size of the above-mentioned foam material is less than 200 μm, and has good pore uniformity and size uniformity, which can improve the appearance of the earphone ear caps; (2) The above-mentioned foam material has good air permeability and water permeability, which can ensure the dryness and freshness of the ear canal (after wearing it for 1 hour (h), the humidity of the ear canal is within 85% (i.e., not more than 85%), and compared with conventional ear caps, the humidity of the ear canal is reduced by more than 10%), which is healthier; (3) The above-mentioned foam material has good slow rebound characteristics (the rebound recovery time is not less than 4 seconds), which is more comfortable; (4) The surface viscosity of the above-mentioned foam material is low, which can reduce the surface stickiness of the earphone ear cap, making the earphone ear cap smooth and resistant to dirt, and solving the problem of stickiness and easy dirtiness of the earphone ear cap; (5) The molecular weight of the above-mentioned foam material contains antibacterial agent components, which can improve the antibacterial property of the earphone ear cap, and the antibacterial rate can reach 90%, or even 95% or 96% or more.
[0101] In specific implementation, the distribution and size of the bubbles in the cross section of the bottom of the ear cap or any area of the headphone can be monitored by an optical microscope (such as a scanning electron microscope (SEM)). Studies have shown that the bubbles in the above-mentioned foaming material are evenly distributed and uniform in size, and the size of the largest bubble is less than 200μm, that is, the size of the bubbles in the foaming material is distributed within the range below 200μm.
[0102] In addition, the fluorinated layer of the above-mentioned foaming material, as well as the surface hydrophobic angle (water contact angle) and other properties can also be measured by conventional methods in the art. For example, by performing elemental analysis on the surface of the foaming material by X-ray photoelectron spectroscopy (XPS) analysis, it is measured that the surface contains fluorine element and forms a fluorinated layer.
[0103] The embodiment of the present application also provides a method for preparing the above composite material, comprising the following steps: forming a foaming material on the surface of a substrate according to the above method for preparing a foaming material to obtain a composite material.
[0104] Specifically, after the adhesive is applied to the surface of the substrate, the polyether polyol and the MDI-based isocyanate are cross-linked and gelled on the surface of the substrate in the presence of an antibacterial agent, a catalyst and a foam leveling agent in a non-aqueous environment. In specific implementation, after the adhesive is applied to the surface of the substrate, the second mixed system is subjected to a shaping treatment on the surface of the substrate to form a gel-type precursor; and the gel-type precursor is subjected to the above-mentioned surface fluorination treatment to form the above-mentioned foaming material on the surface of the substrate to obtain a composite material.
[0105] As mentioned above, the cross-linked gel process can be carried out in a mold to form a polyurethane foam material on a substrate to obtain a composite material product of a preset shape (such as an earphone ear cap), that is, a composite material product of a preset structure can be formed by using a mold, and the mold used may include a male mold and a female mold, and the male mold is provided with a substrate, and the second mixed system is injected into the female mold with a preset shape, and the mold temperature is maintained at a preset shaping treatment temperature (40°C to 60°C), and a shaping treatment is performed in the mold, that is, gel and pore growth shaping is performed, and after the shaping treatment is completed, the mold is opened, and a composite material intermediate having a preset shape (the above-mentioned gel-type intermediate is formed on its substrate) is taken out, and then the composite material intermediate is placed in a heating device such as an oven for aging treatment to obtain a composite material precursor (the above-mentioned gel-type precursor is formed on its substrate); then the composite material precursor is fluorinated to form a fluorinated layer on the surface of the gel-type precursor on its substrate, that is, a composite material is obtained.
[0106] In specific implementation, the outer surface of the substrate can be cleaned with solvents such as ethanol, and after air drying, a glue material (adhesive) is brushed on the outer surface of the substrate. After the glue dries (specifically, it can be dried naturally), the substrate is placed on the male mold, the second mixed system is injected into the mold cavity female mold, and then the mold is closed for shaping. After the shaping treatment is completed, the mold is opened to obtain an integrated composite material intermediate (the gel-type intermediate and the substrate are bonded by the bonding layer formed by the above-mentioned glue material).
[0107] In addition, the prepared composite materials such as headphone ear caps (or composite material precursors) can be cut or processed to form foam material products of preset shapes. For example, the bottom of the above-mentioned headphone ear caps can be cut to make the bottom flat, thereby obtaining polyurethane foam ear caps with a flat bottom.
[0108] In addition, the above-mentioned substrate can be a conventional material suitable for headphone ear caps in the art, which can be prepared by conventional methods in the art, for example, pouring the liquid into a mold and solidifying it to form a substrate, wherein the liquid can include silicone oil, such as vinyl silicone oil and hydrogen-containing silicone oil without double bonds, etc., and there is no special limitation on this.
[0109] The present invention is further described below through specific examples. Unless otherwise specified, the raw materials or reagents used can be obtained commercially, among which:
[0110] The first polyether polyol was purchased from Jiahua Chemical Co., Ltd. under the trade name VE7321, and its hydroxyl value was 238 mgKOH / g;
[0111] The second polyether polyol was purchased from Jiahua Chemical Co., Ltd. under the trade name Puranol F 1623, with a hydroxyl value of 33.5 mg KOH / g;
[0112] The third polyether polyol was purchased from Jiahua Chemical Co., Ltd. under the trade name Puranol PP2045B, with a hydroxyl value of 27 mg KOH / g;
[0113] The foam leveling agent is polyether-modified siloxane purchased from Evonik Specialty Chemicals (Shanghai) Co., Ltd., trade name TEGOSTABB 8930;
[0114] The MDI-based isocyanate was modified isocyanate 8019 purchased from Wanhua Chemical Group Co., Ltd., and the NCO group content was 26-27%;
[0115] The organic bismuth catalyst was purchased from Momentive High-Tech Materials Group Co., Ltd., trade name MC-710;
[0116] The tertiary amine catalyst was purchased from Evonik Specialty Chemicals (Shanghai) Co., Ltd. under the trade name NE 1550;
[0117] The adhesive (glue) was purchased from Magotan Company with the trade name MW-221.
[0118] In the following embodiments and comparative examples, the earphone ear caps were prepared by the following process:
[0119] Mixing polyether polyol, ε-polylysine (antibacterial agent), catalyst and foam leveling agent to obtain a first mixed system;
[0120] The first mixed system is placed in a first material tank, and the temperature of the first material tank is controlled to be about 50°C; the MDI isocyanate is placed in a second material tank, and the temperature of the second material tank is controlled to be about 50°C;
[0121] The first mixed system in the first material tank and the MDI-based isocyanate in the second material tank are pumped into the mixing head by a pump for mixing, and air is pumped into the mixing head by a pump for mixing, so as to obtain a second mixed system;
[0122] The outer surface of the silicone substrate is cleaned with ethanol, and after air drying, a binder is applied to the outer surface of the silicone substrate. After the binder is naturally dried, the silicone substrate is placed on the male mold of the mold, and the second mixed system is injected into the female mold, and then the mold is closed for shaping treatment, wherein the mold temperature is maintained at about 50° C. After the shaping treatment for 10 minutes, the mold is opened to obtain an integrated composite material intermediate;
[0123] The composite material intermediate is placed in an oven and cured at 60° C. for about 30 minutes to obtain a composite material precursor;
[0124] cutting the bottom of the composite material precursor to form a composite material precursor with a flat bottom;
[0125] The composite material precursor is placed in a kettle, a mixed gas of fluorine and oxygen is introduced into the kettle, and the mixture is treated at 50° C. for about 20 minutes to obtain a composite material. Figure 6 The headphone ear caps are shown.
[0126] In each embodiment and comparative example, the amount of polyether polyol, the amount of MDI-based isocyanate, the amount of foam leveling agent, the type and amount of catalyst, etc. are shown in Table 1 and Table 2. Except for the differences shown in Table 1 and Table 2, the other conditions are the same.
[0127] In addition, the cell size uniformity, surface stickiness, slow rebound properties and antibacterial properties of the earphone ear caps prepared in each embodiment and comparative example were evaluated by the following process, and the results are shown in Table 1 and Table 2:
[0128] <Evaluation of Cell Size Uniformity>
[0129] The ear cap of the headphone was cut open with a utility knife, and the cut section (cross section) and the pore morphology at the bottom of the ear cap were observed under an optical microscope at a magnification of 100 times. The pore size was counted, and the pore size of a certain area was counted and converted into an average of 1 cm 2 The number of cells within the area and with a size within the corresponding range, the evaluation criteria are as follows:
[0130] ◎: The maximum cell size is less than 200 μm (no cells larger than 200 μm were observed, i.e., the average cell size per 1 cm 2The number N of cells with a size greater than 200 μm in the area is substantially equal to 0);
[0131] ○: The maximum cell size is between 200 and 300 μm (average per 1 cm 2 The number of cells with a size between 200 and 300 μm in the area is greater than 1, and no cells with a size greater than 300 μm are observed);
[0132] △: The maximum cell size is between 300 and 500 μm (average per 1 cm 2 The number of cells with a size between 300 and 500 μm in the area is greater than 1, and no cells with a size greater than 500 μm are observed);
[0133] ×: The maximum cell size is greater than 500 μm (average per 1 cm 2 The number of cells with a size greater than 500 μm in the area is greater than 1), or the cells are collapsed.
[0134] <Surface Tackiness Evaluation>
[0135] Lower the bottom of the earphone ear cap, sprinkle dust on the ear cap (polyurethane foam surface), and then use a hair dryer to blow it away; then observe it under a microscope with a magnification of 200 times, and evaluate and determine the attachments on the polyurethane foam surface. The evaluation criteria are as follows:
[0136] ○: There is no dust on the surface of the ear cap;
[0137] △: There is a little dust on the surface of the ear cap;
[0138] ×: There is a lot of dust on the surface of the ear cap.
[0139] <Evaluation of Slow Rebound Characteristics>
[0140] According to the above preparation process, a layered polyurethane foam (or polyurethane foam layer) is obtained, and it is squeezed to the maximum extent with fingers (but without destroying the polyurethane foam), and then released, and the time for the foam to return to the initial state (i.e., the original natural state) (i.e., the rebound recovery time) is recorded. The evaluation criteria are as follows:
[0141] ○: The time to return to the initial state is more than 6 seconds;
[0142] △: The time to return to the initial state is between 3 and 6 seconds;
[0143] ×: The time to return to the initial state is less than 3s.
[0144] <Evaluation of antibacterial properties>
[0145] LB liquid medium was used to prepare 105 CFU / mL of Escherichia coli solution, for later use;
[0146] Experimental group: referring to the above preparation process, the second mixed system was poured into a polytetrafluoroethylene mold with a size of 100mm×100mm×5mm, and after being cured by the above directional treatment process, the above aging treatment (i.e., aging at 60°C for 30min) was performed; the polyurethane foam sample was then cut into samples with a size of 20mm×20mm (remaking the polyurethane foam sample through this process facilitates the formation of samples of the required shape and size, which is convenient for testing, and the antibacterial rate test results are consistent with the earphone ear caps prepared under the same conditions above); the sample was first disinfected with alcohol, and then the bacteria were cultured on the surface of the sample (i.e., 200μL of Escherichia coli solution was dripped into the middle of the sample (the solution did not overflow the edge of the sample), and then placed in a 37°C constant temperature incubator for static culture), and the culture time was 24h; after the culture was completed, the number of Escherichia coli was observed under a microscope, and the concentration of the solution x1 was obtained according to the observation results;
[0147] Control group: No polyurethane foam sample was added, and the other conditions were basically the same as those of the experimental group; after the culture was completed, the bacterial solution concentration x0 was obtained;
[0148] The antibacterial rate y is calculated according to the formula y = (1-x1 / x0) × 100%, and the evaluation criteria are as follows:
[0149] Antibacterial property: antibacterial property is greater than 90% (i.e. y>90%);
[0150] No antibacterial property: The antibacterial property is less than 50% (i.e. y<50%).
[0151] Table 1
[0152]
[0153] Table 2
[0154]
[0155] It can be seen that, compared with Comparative Examples 1 to 4, the polyurethane foam in the earphone ear caps prepared in Examples 1 to 5 has good uniformity of pore size, good slow rebound characteristics (rebound recovery time is not less than 4s), low surface viscosity and antibacterial properties. Among them, in Examples 1 to 5, the surface water contact angle of the polyurethane foam is measured to be greater than 90°, and the size of the pores in the polyurethane foam is between 10 μm and 161 μm.
[0156] In addition, it can be seen from Comparative Example 1 that no antibacterial agent is added and the polyurethane foam does not have antibacterial properties.
[0157] In addition, it can be seen from Comparative Example 2 that no fluorination treatment was performed and the surface of the polyurethane foam was very sticky.
[0158] In addition, it can be seen from Comparative Example 3 that no foam leveling agent is added and the pore size uniformity of the polyurethane foam is poor.
[0159] In addition, it can be seen from Comparative Example 4 that DBU catalyst is used to replace the organic bismuth catalyst and the tertiary amine catalyst, the pore size uniformity of the polyurethane foam is poor, pore collapse occurs, and the rebound recovery time is long (≤1s), and the slow rebound characteristics are poor; in addition, no antibacterial agent is added, and the polyurethane foam does not have antibacterial properties.
[0160] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A foaming material, characterized in that: The invention comprises a polyurethane matrix and an antibacterial agent in the polyurethane matrix. The surface water contact angle of the foaming material is greater than 90 degrees. The foaming material has pores, and the size of the pores is less than 200 μm.
2. The foam material according to claim 1, characterized in that: The size of the cells in the foamed material is between 10 μm and 161 μm.
3. The foaming material according to claim 1, characterized in that: The foaming material is a slow-rebound sponge, and its rebound recovery time is not less than 4 seconds.
4. The foam material according to claim 1, characterized in that: The antimicrobial agent includes ε-polylysine.
5. The foam material according to claim 1, characterized in that: The invention also contains a catalyst in the polyurethane matrix, wherein the catalyst comprises an organic bismuth catalyst and a tertiary amine catalyst.
6. The foam material according to claim 1, characterized in that: The invention also contains a foam stabilizer in the polyurethane matrix, wherein the foam stabilizer comprises polyether-modified siloxane.
7. The foaming material according to any one of claims 1 to 6, characterized in that: The raw materials of the polyurethane matrix include polyether polyol and MDI-based isocyanate, wherein the polyether polyol includes a first polyether polyol with a hydroxyl value of (228-248) mg KOH / g, a second polyether polyol with a hydroxyl value of (28-40) mg KOH / g, and a third polyether polyol with a hydroxyl value of (22-32) mg KOH / g.
8. The foam material according to claim 7, characterized in that: The ratio of the mass of the first polyether polyol to the total mass of the polyether polyol is (65-95):100; and / or, The ratio of the mass of the second polyether polyol to the total mass of the polyether polyol is (2.5-17.5):100; and / or, The ratio of the mass of the third polyether polyol to the total mass of the polyether polyol is (2.5-17.5):
100.
9. The foam material according to claim 1, characterized in that: A fluorinated layer is formed on the surface of the foamed material.
10. A method for preparing a foaming material according to any one of claims 1 to 9, characterized in that: The following steps are involved: The polyether polyol and MDI-based isocyanate are cross-linked and gelled in the presence of an antibacterial agent, a catalyst and a foam leveling agent in a non-aqueous environment, and gas is introduced therein to form pores, thereby obtaining a gel-type precursor having pores; Performing surface fluorination treatment on the gel-type precursor to obtain the foaming material; in, The polyether polyol comprises a first polyether polyol having a hydroxyl value of (228-248) mg KOH / g, a second polyether polyol having a hydroxyl value of (28-40) mg KOH / g, and a third polyether polyol having a hydroxyl value of (22-32) mg KOH / g; The catalyst includes an organic bismuth catalyst and a tertiary amine catalyst.
11. The method for preparing a foaming material according to claim 10, characterized in that: The ratio of the mass of the first polyether polyol to the total mass of the polyether polyol is (65-95):100; and / or, The ratio of the mass of the second polyether polyol to the total mass of the polyether polyol is (2.5-17.5):100; and / or, The ratio of the mass of the third polyether polyol to the total mass of the polyether polyol is (2.5-17.5):
100.
12. The method for preparing a foaming material according to claim 10, characterized in that: The antimicrobial agent includes ε-polylysine.
13. The method for preparing a foaming material according to claim 10, characterized in that: The foam leveling agent includes polyether-modified siloxane.
14. The method for preparing a foaming material according to claim 10, characterized in that: The process of cross-linking the gel comprises: Mixing the polyether polyol, the antibacterial agent, the catalyst and the foam leveling agent to obtain a first mixed system; Mixing the first mixed system with the MDI-based isocyanate and introducing the gas thereinto to obtain a second mixed system; The second mixed system is subjected to a shaping treatment, and the gel and pore growth are shaped by the shaping treatment to obtain a gel-type intermediate having pores formed therein; The gel-type intermediate is subjected to an aging treatment to obtain the gel-type precursor.
15. The method for preparing a foamed material according to claim 14, characterized in that: The conditions of the shaping treatment are: temperature of 40°C to 60°C and time of 10min to 20min; And / or, the aging treatment conditions are: temperature of 60° C. to 80° C., and time of 30 min to 60 min.
16. The method for preparing a foaming material according to claim 10, characterized in that: The gel-type precursor is contacted with a mixed gas containing fluorine gas and oxygen to perform the surface fluorination treatment, and / or The temperature of the surface fluorination treatment is 40° C. to 60° C., and the time of the surface fluorination treatment is 10 min to 30 min.
17. A composite material, characterized in that: It comprises a substrate and a foam material present on the surface of the substrate, wherein the foam material comprises the foam material according to any one of claims 1 to 9 or the foam material prepared according to the preparation method according to any one of claims 10 to 16.
18. The composite material according to claim 17, characterized in that The composite material is an earphone ear cap, or a sponge pad used for a wearable augmented reality device or a wearable virtual reality device.
19. A wearable device, characterized in that: Comprising the composite material according to claim 17 or 18.
20. The wearable device according to claim 19, characterized in that: The wearable device includes a headset, a wearable augmented reality device or a wearable virtual reality device.
21. A method for preparing the composite material according to claim 17 or 18, characterized in that: The method comprises the following steps: forming the foaming material on the surface of the substrate according to the preparation method described in any one of claims 10 to 16 to obtain the composite material.
22. The method for preparing a composite material according to claim 21, characterized in that: After the adhesive is coated on the surface of the substrate, the polyether polyol and the MDI-based isocyanate are cross-linked and gelled on the surface of the substrate in the presence of an antibacterial agent, a catalyst and a foam leveler in a non-aqueous environment.